1 / 13

130 likes | 275 Vues

You Will Be Able To:. Solve systems with Substitution. Solve Systems by Substitution: Solve for either x or y in one equation Substitute the expression into the other equation Solve the equation Substitute answer back into 1 st equation Solve for other variable

Télécharger la présentation
## You Will Be Able To:

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**You Will Be Able To:**Solve systems with Substitution**Solve Systems by Substitution:**• Solve for either x or y in one equation • Substitute the expression into the other equation • Solve the equation • Substitute answer back into 1st equation • Solve for other variable • Write answer as ordered pair (x,y)**Ex #1: Tell which equation you would use to isolate the**variable. Explain your reasoning. 1st one a. x is by itself**Ex #1: Tell which equation you would use to isolate the**variable. Explain your reasoning. 1st one b. y is by itself**Ex #1: Tell which equation you would use to isolate the**variable. Explain your reasoning. c. 2nd one Only need to subtract 4x to get “y” by itself**Ex #2: Solve the system using substitution**y = 3(1) + 2 y = 3 + 2 y = 5 x + 2(3x + 2) = 11 + 4 = 11 x + 6x 7x + 4 = 11 7x = 7 (1, 5) x = 1**b.**x = -3 + 3 x = 0 y+3 + 2y = -6 3y + 3 = -6 3y = -9 y = -3 (0, -3)**c.**y = 2(1) + 5 y = 2 + 5 3x + 2x+5 = 10 y = 7 5x + 5 = 10 5x = 5 x = 1 (1, 7)**d.**x = 1 – 2(1) x = 1 – 2 x = -1 2(1–2y) – 3y = -5 2 – 4y – 3y = -5 -7y + 2 = -5 -7y = -7 y = 1 (-1, 1)**Ex #3: Solve the system using substitution**x = 2y – 6 x = 2(2) – 6 x = 4 – 6 x = -2 4(2y–6) + 6y = 4 8y – 24 + 6y = 4 14y – 24 = 4 14y = 28 (-2, 2) y = 2**b.**y = -6x – 1 y = -6(-1) – 1 y = 6 – 1 y = 5 3x + 2(-6x-1) = 7 = 7 – 2 3x – 12x -9x – 2 = 7 -9x = 9 x = -1 (-1, 5)**Ex #3: Write a system and solve.**During a football game, the parents of the football players sell pretzels and popcorn to raise money for new uniforms. They charge $2.50 for a bag of popcorn and $2 for a pretzel. The parents collect $336 in sales during the game. They sell twice as many bags of popcorn as pretzels. How many bags of popcorn do they sell? x = popcorn = 336 2.50x + 2y y = pretzels x = 2y**= 336**2.50x + 2y x = 2y 2(48) x = 96 x = = 336 2.50(2y) + 2y 5y = 336 + 2y 7y = 336 y = 48 96 bags

More Related